The Relationship Between Pre-Conception Nutritional Care Patterns and ANC Frequency with Stunting Incidence in Newborns: A Prospective Cohort Study in North Sumatra - Suryani, Elvi (The Indonesian Institute of Science and Technology Research, 2025)
Stunting remains a critical public health challenge in Indonesia, with North Sumatra showing particularly high prevalence rates. Pre-conception nutrition and antenatal care (ANC) frequency are potentially modifiable factors that may influence birth outcomes and subsequent growth patterns. To examine the relationship between pre-conception nutritional care patterns and ANC frequency with stunting incidence in newborns using a mixed-methods prospective cohort design in North Sumatra. A prospective cohort study was conducted involving 1,200 women of reproductive age (18-35 years) who intended to conceive, recruited from primary healthcare centers across North Sumatra. Participants were followed from pre-conception through 24 months post-delivery. Pre-conception nutritional assessment included body mass index (BMI), mid-upper arm circumference (MUAC), hemoglobin levels, and dietary intake patterns. ANC frequency and quality were monitored throughout pregnancy. Birth outcomes and child growth measurements were assessed at birth, 6, 12, 18, and 24 months. Qualitative interviews were conducted with a subsample of 60 mothers to explore perceptions and experiences regarding nutrition and healthcare utilization. The overall stunting prevalence at 24 months was 28.3%, consistent with national averages. Mothers with optimal pre-conception nutrition status (adequate BMI ≥18.5 kg/m², MUAC ≥23.5 cm, hemoglobin ≥12 g/dL) had significantly lower risk of having stunted children (adjusted OR: 0.65, 95% CI: 0.48-0.87, p<0.01). Adequate ANC visits (≥6 visits) were associated with 18% lower risk of stunting (adjusted OR: 0.82, 95% CI: 0.68-0.99, p<0.05). Qualitative findings revealed significant knowledge gaps regarding pre-conception nutrition importance and cultural barriers to optimal healthcare utilization. Pre-conception nutritional status and adequate ANC frequency are significant protective factors against stunting in North Sumatra. Integrated interventions targeting both pre-conception health optimization and improved ANC utilization may substantially reduce stunting prevalence.